2018
DOI: 10.1016/j.enpol.2017.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Green transition of energy systems in rural China: National survey evidence of households’ discrete choices on water heaters

Abstract: Energy systems in rural China are experiencing a transition from traditional fossil fuels to renewables. This paper aims to investigate the potential factors that influence the choices of rural residents regarding water heaters with a focus on the low-carbon transition to solar water heating systems. To this end, a face-to-face questionnaire survey is undertaken with 3404 rural households randomly selected among 12 representative provinces. A comprehensive set of discrete choice modelling approaches were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Based on the feedback, we refined our survey questionnaire and decided on the final version during the spring of 2016. The respondents were recruited via WeChat, the most popular social media platform in Chinese consumers, urban residents in China often have more knowledge than rural residents and thus more likely to purchase and benefit from energy saving appliances (Ma et al 2018).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the feedback, we refined our survey questionnaire and decided on the final version during the spring of 2016. The respondents were recruited via WeChat, the most popular social media platform in Chinese consumers, urban residents in China often have more knowledge than rural residents and thus more likely to purchase and benefit from energy saving appliances (Ma et al 2018).…”
Section: Data Collectionmentioning
confidence: 99%
“…Therefore, a higher urban representation in our dataset enables us to gather as much as possible 10 information on how to promote energy-saving appliances. We recognize the cross-country heterogeneity in the urban-rural divide, for example between China (Ma et al 2018) and India (Parikh and Parikh 2016), and thus limit our interpretations only to what our sample represents. "…”
Section: Data Collectionmentioning
confidence: 99%
“…Similar findings were made by Shen, et al (2015) in China, who discovered a link between families using clean fuel for cooking and public awareness, household characteristics, family size and age. A different study carried out in China by Ma, et al (2018) found that socio-economic determinants had a favorable, significant impact on resident first-stage LPG and electricity choice. Zhang and Koji (2017) found that LPG was preferred as a cooking fuel in homes in Northern China with per capita incomes over 4,000 RMB.…”
Section: East African Journal Of Education and Social Sciencesmentioning
confidence: 98%
“…Meanwhile, due to the difference in China's regional economic development, population scale, and other aspects, it is necessary to develop relevant electricity policies suitable for the actual situation of local regions. Ma et al [28] explored the two behavioral mechanisms of rational decision-making and inertia decision-making in the process of residents' power consumption based on the perspective of residents' rational consumption. It has been found that income affects significantly residents' electricity consumption, and living habits have an important impact on consumption behavior [29].…”
Section: Literature Reviewmentioning
confidence: 99%